The Tillman story [videorecording (DVD)] - Bar-Lev, Amir; Brolin, Josh (Sony Pictures Home Entertainment, 2011)
Pat Tillman chose to walk away from a multimillion-dollar football contract and join the military for no other reason than he felt it was the right thing to do. Documented are the facts surrounding the way the military manipulated his tragic death in the line of duty into a propaganda tool, which is totally unfathomable.